Rancang Bangun Sistem Informasi Monitoring Pembayaran Angsuran Nasabah Bank Mandiri - Andri Cahyo Purnomo; Sri Wahyuni; Andi Aruan (UNIVERSITAS RAHARJA, 2021)
Computers are electronic devices for processing data used by banks, government and other private institutions. The use of this computer must be in accordance with the needs of the organization that uses it, both software and hardware so that the computer can be used as well as possible. Bank Mandiri is a state-owned bank engaged in services, of course, wants to provide the best service for its customers. In providing information about installments at Bank Mandiri Unit Cikupa Niaga Mas 2 (CNM 2), currently it has a computerized system and is running well, but only independent bank employees can use the system, while debtors still use the manual system. using HVS paper as an information medium. A system that can provide information about debtor installments quickly and accurately is needed. This study is interested in discussing the installment data information system for Bank Mandiri Cikupa Niaga Mas 2 (CNM 2) customers which aims to optimize the provision of better information services for customers of Bank Mandiri Cikupa Niaga mas 2 (CNM 2). In this study, using the analysis of the pieces method, the authors can easily identify the weaknesses that exist in the old system which results in recommendations for system improvements based on indicators of Performance, Information, Economic, Control, Efficiency, and Service, then to make a design. In the new system, researchers use object-oriented modeling, namely UML (Unified Modeling Language) which is the right tool to use in describing the design of the system that will be loaded according to user needs. It is hoped that the Bank Mandiri customer installment system will make it easier for customers to find out about the ongoing installments.